Analisis Kualitas Pelayanan Terhadap Loyalitas Nasabah Pada BANK MUAMALAT Indonesia Cabang Pekanbaru - Rahayu, Deny Danar; Alwie, Ahi Furwanti (Jurnal Ekonomi, 2010)
This paper examines the multidimensionality of service quality model in Islamicbanking industry. It adapts the CARTER measure of the importance of servicequality items in one of the leading Islamic bank The analysis uses mehod calledfactor analysis to find out whether all CARTER items loaded positively or not.The findings suggestthat CARTER models is multidimensional and providesdifferent implications for both managers and academic researchers. Themanagers should be aware of religious factors which loaded first and rated thehighest important in the scale and improve ways of providing products andservice to customers.